A rowing-specific mindfulness intervention: Effects on mindfulness, flow, reinvestment, and performance - Sparks, Katherine V.; Ring, Christopher (Frontiers in Psychology, 2022)
Mindfulness can benefit athletes’ mindset and performance. These benefits may be enhanced by sport-specific mindfulness interventions. Accordingly, our objectives were twofold. First, to develop a rowing-specific mindfulness intervention, and second, to investigate its effects on mindfulness, flow, reinvestment, and rowing performance. Rowers were randomly assigned to either a 6-week rowing-specific mindfulness intervention (n = 23), which included generic and rowing-specific practices, or a control group (n = 21). Rowers completed pre-test and post-test measures of performance, mindfulness, flow, and rowing-specific reinvestment. Lastly, rowers completed an evaluation form following the intervention. The results demonstrated that the intervention group increased flow, mindfulness and improved performance, additionally conscious motor processing decreased from pre-test to post-test. However, the intervention did not preferentially change mindfulness or reinvestment compared to control. Participants provided favourable feedback and evaluated the intervention positively. Our 6-week rowing-specific mindfulness intervention promoted flow, encouraged mindfulness, and aided performance. Thus, we provide preliminary explorative evidence that a sport-specific mindfulness intervention can benefit athletes. We recommend that future research, with large sample sizes and improved home practice, should examine mediators and moderators of the mindfulness-performance relationship.